Analisis Pelaksanaan Pajak Penghasilan Orang Pribadi (pph21) Menurut Ekonomi Islam - Qorien Arifah Elhany Mahaka; Havizon Havizon; Lucy Auditya (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Personal income tax (PPh 21) is a mandatory levy relating to income earned by an individual taxpayer through the work, services or activities he is doing. The research was conducted with the aim of knowing the implementation of taxes (PPh 21) in the context of Islamic economics. The method used in this study is a qualitative method which is included in library research, namely the research sources come from books, previous research, journals, and the internet. From all these sources, then processed to be analyzed in order to get a conclusion. The results of this study are that the determination of progressive rates on personal income tax (PPh 21) is allowed in Islam for considerations of justice and benefit and personal income tax (PPh 21) meets the principle of tax collection (dharibah) in Islamic economics so that the tax may be taken. Keywords: PPh 21, progressive rates, principle of collection